The Pollutant Organotins Leads to Respiratory Disease by Inflammation: A Mini-Review - Nunes-Silva, Albená; Dittz, Dalton; Santana, Higor Scardini; Faria, Rodrigo Alves; Freitas, Katia Michelle; Coutinho, Christiane Rabelo; de Melo Rodrigues, Livia Carla; Miranda-Alves, Leandro; Silva, Ian Victor; Graceli, Jones Bernardes; Freitas Lima, Leandro Ceotto (Frontiers in Endocrinology, 2018)
Organotins (OTs) are organometallic pollutants. The OTs are organometallic pollutants that are used in many industrial, agricultural and domestic products, and it works as powerful biocidal compound against large types of micro-organisms such as fungi and bacteria. In addition, OTs are well known to be endocrine-disrupting chemicals (EDCs), leading abnormalities an “imposex” phenomenon in the female mollusks. There are some studies showing that OTs exposure is responsible for neural, endocrine, and reproductive dysfunctions in vitro and in vivo models. However, OTs effects over the mammalian immune system are poorly understood, particularly in respiratory diseases. The immune system, as well as their cellular components, performs a pivotal role in the control of the several physiologic functions, and in the maintenance and recovery of homeostasis. Thus, it is becoming important to better understand the association between environmental contaminants, as OTs, and the physiological function of immune system. There are no many scientific works studying the relationship between OTs and respiratory disease, especially about immune system activation. Herein, we reported studies in animal, humans and in vitro models. We searched studies in PUBMED, LILACS and Scielo platforms. Studies have reported that OTs exposure was able to suppress Th1 and exacerbate Th2 response in the immune system. In addition, OTs contact could elevate in the airway inflammatory response, throughout a mechanism associated with the apoptosis of T regulatory cells and increased oxidative stress response. In addition, OTs induce macrophage recruitment to the tissue, leading to the increased necrosis, which stimulates an inflammatory cytokines secretion exacerbating the local inflammation and tissue function loss. Thus, the main intention of this mini-review is to up to date the main findings involving the inflammatory profile (especially Th1 and Th2 response) in the respiratory tract as a result of OTs exposure.